2017
DOI: 10.1016/j.redox.2017.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of methysticin improves cognitive deficits in a mouse model of Alzheimer's disease

Abstract: IntroductionThere is increasing evidence for the involvement of chronic inflammation and oxidative stress in the pathogenesis of Alzheimer's disease (AD). Nuclear factor erythroid 2-related factor 2 (Nrf2) is an anti-inflammatory transcription factor that regulates the oxidative stress defense. Our previous experiments demonstrated that kavalactones protect neuronal cells against Amyloid β (Aβ)-induced oxidative stress in vitro by Nrf2 pathway activation. Here, we tested an in vivo kavalactone treatment in a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 31 publications
0
48
0
Order By: Relevance
“…Oral administration of the kavalactone methysticin (Fig. ) activated the Nrf2 pathway in the hippocampus and cortex of AD (APP/Psen1) mice . This treatment reduced microgliosis, astrogliosis, and the secretion of the proinflammatory cytokines TNF‐α and IL‐17A, as well as oxidative damage.…”
Section: Role Of Nrf2 In Neuroinflammationmentioning
confidence: 97%
“…Oral administration of the kavalactone methysticin (Fig. ) activated the Nrf2 pathway in the hippocampus and cortex of AD (APP/Psen1) mice . This treatment reduced microgliosis, astrogliosis, and the secretion of the proinflammatory cytokines TNF‐α and IL‐17A, as well as oxidative damage.…”
Section: Role Of Nrf2 In Neuroinflammationmentioning
confidence: 97%
“…Low-grade systemic inflammation was observed in the serum of SAMP8, whereas salidroside was able to decreased the levels of proinflammatory cytokines, IL-1α, IL-6, IL-17A and IL-12. Notably, the elevated levels of these four proinflammatory cytokines are reported to be involved in the subsequent cognitive decline or pathology of AD [37][38][39][40] . Primarily based on murine models, Th1 cells significantly accelerates markers of Alzheimer's disease [41] , and Th17 cells have also been described to induced severe fluctuation in neuronal intracellular Ca(2+) concentration, causing neuronal damage and neuroinflammation in vivo imaging experiments [42] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the action of Piper methysticum in experimental models of neurodegenerative diseases, specifically in AD, demonstrating the neuroprotective effect of this herbal medicine [15][16][17].…”
Section: Neuroprotective Effect Of Extractsmentioning
confidence: 99%
“…Recent studies, such as Fragoulis et al have shown that one of the possible explanations for the action of piper mechanism in AD is associated with the activation of the erythroid2-related nuclear factor (NrF2) [15].…”
Section: Neuroprotective Effect Of Extractsmentioning
confidence: 99%